Analisis Manajemen Risiko Pengelolaan Wakaf Pada Kantor Urusan Agama Kecamatan Payakumbuh Timur (Studi Pengelolaan Wakaf Tanah) - Tesa Dwi Ningsih; Rizal Rizal; Chitra Indah Sari; Widi Nopiardo (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this research is the source of risk that occurs in the management of waqf at the East Payakumbuh District Religious Affairs Office. The type of research that the author uses is field research with a qualitative approach research method. Data collection techniques through interviews and documentation. Meanwhile, the data analysis technique is by reducing data, presenting data and drawing conclusions. The results of this research show that there are 13 risks faced in the management of land waqf in the KUA of East Payakumbuh District and the form of control by conducting outreach to the wakif so that the wakif understands land waqf, holding meetings between the Head of the KUA of East Payakumbuh District and his Deputy. East Payakumbuh District KUA recommends to the wakif that the documents be completed. and the KUA takes the documentation at the time of the waqf pledge, keeps the documentation so that it is not lost and the KUA also advises the wakif to make a land certificate to the land institution so that the waqf land can be donated.